Hyperinflammatory status associated with COVID-19: clinical and histopathology features of a pediatric series - Leite, Douglas Squizatto; Côrtes, Lucas Silva; Domingues, Maria Aparecida Custodio; Magalhães, Claudia Saad; Fernandes, Taciana de Albuquerque Pedrosa (Springer Nature, 2024)
Objective: Explore clinical, demographic and histopathologic features of pediatric hyperinflammatory manifestations associated to SARS-CoV-2, observed during the COVID-19 pandemic, and the relationship of Multisystemic Inflammatory Syndrome of Childhood (MIS-C) with other inflammatory and autoimmune manifestations, such as macrophage activation syndrome, vasculitis and vasculopathy.
Methods: A protocol with detailed socio-demographic and clinical features, SARS-CoV-2 exposure and morbidity was conducted in a public tertiary hospital as part of a multicentric international protocol. Cases were selected and enrolled in a single centre from 2020 to 2022, recording all the organ and systems manifestations, standard treatment and outcome.
Results: Of the 23 suspicious cases, 21 met the inclusion criteria of MIS-C. Gastrointestinal manifestations were frequent, and three out of 21 had acute abdomen, one with documented histiocytic necrotizing lymphadenopathy (HNL), 3 had macrophage activation syndrome (MAS), and one case, with previous enthesitis related arthritis evolved into type V Takayasu arteritis and malignant hypertension. All patients were treated with either intravenous immunoglobulin (IVIG), high dose glucocorticoids or both, five were under intensive care treatment with respiratory and cardio-circulatory support. All had full recovery during acute phase. Description the HNL histopathology showed proliferation of small lymphocytes and macrophage infiltrates with microthrombi and lymph nodes germinal centers necrosis.
Conclusion: Post-infectious hyperinflammatory states associated with COVID manifestations may cause not only to transient inflammatory features, but also autoimmunity, vasculitis and vasculopathy manifestations that require prompt treatment.